My man Godfrey - Hatch, Eric; Previn, Charles 1888-1973 (Criterion Coll., 2001)
A zany millionaire family invites a tramp to be their butler.
Bildformat 1.33:1
Orig.: USA 1936
Enth. audio commentary by film historian Bob Gilpin ; rare outtakes ; the complete 1938 broadcast of the Lux Radio Theater adaption, starring Powell and Lombard ; production stills archive
Keywords: Hatch, Eric <1901-1973> -- Film and video adaptations; Hatch, Eric -- 1901-1973; Social classes - United States - Drama; Household employees -- Drama; Impostors and imposture -- Drama; Man-woman relationships -- Drama; Rich people -- Drama; Social classes -- United States -- Drama; Tramps -- Drama; Haushaltshilfe; Hochstapler; Verfilmung; Millionär; Liebesfilm; Soziale Schichtung; Landstreicher; USA; Film; DVD-Video; Comedy films; Feature films; Screwball comedy films; Video recordings for the hearing impaired